Facultative anaerobic bacteria on dentistry students’ gutta-percha points: The importance of disinfection (2018)
Background: During endodontic treatment in dentistry, if the gutta-percha points contain microorganisms that are resistant to the conditions in the root canal once it is sealed, they can lead to new infections. The purpose of this study was to determine the presence and quantification of facultative anaerobic bacteria in students’ guttapercha points. Methods: A representative sample of dentistry students’ gutta-percha points were collected, together with information on their characteristics. The points were placed in saline solution for inoculation in blood agar followed by anaerobic incubation for five days. Bacteria presence and type were determined, quantified, and identified. Following this, the X2 test was used to verify whether there were any significant differences in the contamination found in the points between the characteristics studied. Results: The results of the microbiological analysis revealed that 32.1% of the points appeared to be contaminated by facultative anaerobic bacteria. The most common types of microorganisms were gram-positive bacilli, followed by gram-positive coccus. Staphylococcus epidermidis was among the microorganisms identified. No relationship was observed between the presence of cone contamination and the characteristics, but a statistically significant difference was detected within the group defined by package opening date. Significant differences were also found in terms of the presence of spore-forming bacilli within the group defined by package opening and expiry date. Conclusions: The presence of facultative anaerobic bacteria of clinical interest in the gutta-percha points used by dentistry students was identified and quantified. Among the bacteria identified, some are of clinical importance, such as Staphylococcus epidermidis and Streptococcus mitis. The establishment of disinfection protocols for such materials is recommended.